2022
DOI: 10.3390/jof8060564
|View full text |Cite
|
Sign up to set email alerts
|

Mating-Type Genes Play an Important Role in Fruiting Body Development in Morchella sextelata

Abstract: True morels (Morchella spp.) are edible mushrooms that are commercially important worldwide due to their rich nutrition and unique appearance. In recent years, outdoor cultivation has been achieved and expanded on a large scale in China. However, the mechanisms of fruiting body development in morels are poorly understood. In this study, the role of mating-type genes in fruiting body development was researched. Fruiting bodies cultivated with different mating-type strains showed no difference in appearance, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Similarly, it has been shown that when cultivated with the spawn of single mating-type strains of mat1-1 or mat1-2, only one corresponding mating-type gene was detected in the mycelium and conidia. However, in contrast, in primordia, pileum and stipe were both MAT (mating types) [ 54 ].…”
Section: Relevance On Biological Research For Steady Cultivation Indu...mentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, it has been shown that when cultivated with the spawn of single mating-type strains of mat1-1 or mat1-2, only one corresponding mating-type gene was detected in the mycelium and conidia. However, in contrast, in primordia, pileum and stipe were both MAT (mating types) [ 54 ].…”
Section: Relevance On Biological Research For Steady Cultivation Indu...mentioning
confidence: 99%
“…Despite the fact that the disproportion between the two mating genotypes was found in a variety of ascomycetes, it seems to be particularly abundant in Morchella [ 55 , 56 ]. We have tested the mating type proportions of commercially cultivated strains.…”
Section: Relevance On Biological Research For Steady Cultivation Indu...mentioning
confidence: 99%
See 2 more Smart Citations
“…(Tan et al, 2019 ; Liu et al, 2020 , 2021a ; Du and Yang, 2021 ; Chai et al, 2022 ). However, there is still a lack of understanding of conidial production, working mechanisms of exogenous nutrition bags, primordium formation, and fruiting body development mechanisms (Liu et al, 2022 ), so basic research should be continued.…”
Section: Focus On Basic Research and Embrace New Breeding Techniquesmentioning
confidence: 99%